Penerapan Manajemen Inovasi pada Startup Mahasiswa Universitas Islam Kebangsaan Indonesia: Penelitian - Agustin Nurhayati; Rahmi; Cut Lika Mestika Sandy; Asmaul Husna; Rahmati (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Student startups have significant potential to grow if supported by effective innovation management. However, many startups at Universitas Islam Kebangsaan Indonesia (UNIKI) still face challenges in managing ideas, prototype development, and business strategies. This community service program aims to implement innovation management through training, mentoring, and evaluation of student startups at UNIKI. The method includes a needs survey, training on innovation management, prototyping workshops, and intensive mentoring for two months. The results indicate an improvement in students' understanding of innovation management, with 60% of startups experiencing an increase in customer acquisition. The program is recommended to continue with strengthening business networks and access to funding.